Perbedaan Kadar Non High Density Lipoprotein Cholesterol pada Mahasiswa Penyandang Obes dan Non Obes - Sri Vanny Suhirman; Efrida Efrida; Rismawati Yaswir (Jurnal Ilmu Kesehatan Indonesia, 2022)
ABSTRACT THE DIFFERENCE OF NON HIGH DENSITY LIPOPROTEIN CHOLESTEROL LEVELS IN OBESE AND NON OBESE STUDENT By Sri Vanny Suhirman Non High Density Lipoprotein Cholesterol was calculated as total cholesterol levels minus HDL levels. Non HDL-C levels can be used as a predictor of cardiovascular disease risk. Non HDL-C levels tend to increase in obese people. This research aims to determine the differences of non HDL-C levels in obese and non obese students. This research was an observational analytic study with a cross sectional design. This research was conducted at the Central Laboratory of Dr. M. Djamil Hospital Padang from July 2020 to February 2021. The sample was 60 students at Faculty of Medicine, Andalas University, consists of 30 obese students and 30 non obese students. Statistical analysis used the independent T-test. The significant test results if the p value <0.05. The results showed that the mean age of the subjects was 20.32±1.05 years. The mean BMI in obese student was 32.53 ± 4.13 kg/m2 and the mean BMI in non obese student was 21.11 ± 1.85 kg/m2. The mean non HDL-C level in the obese student was 131.43 ± 34.70 mg/dL and the mean non HDL-C level in non obese student was 123.93 ± 35.55 mg/dL. Bivariate analysis found that there was no significant difference between the mean non-HDL C levels in the obese student and non obese student (p = 0.412). The conclusion in this research is the mean non HDL-C levels in the obese and non obese student is not different. Keywords: Body mass index, Non High Density Lipoprotein Cholesterol, Obesity